Non-fungible tokens in healthcare: a scoping review - Shahabeddin Abhari; Plinio Morita; Plinio Morita; Plinio Morita; Plinio Morita; Plinio Morita; Pedro Augusto Da Silva E. Souza Miranda; Ali Garavand; Thokozani Hanjahanja-Phiri; Dmytro Chumachenko (Frontiers Media S.A., 2023)
IntroductionNon-Fungible Tokens (NFTs) are digital assets that are verified using blockchain technology to ensure authenticity and ownership. NFTs have the potential to revolutionize healthcare by addressing various issues in the industry.MethodThe goal of this study was to identify the applications of NFTs in healthcare. Our scoping review was conducted in 2023. We searched the Scopus, IEEE, PubMed, Web of Science, Science Direct, and Cochrane scientific databases using related keywords. The article selection process was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA).ResultsAfter applying inclusion and exclusion criteria, a total of 13 articles were chosen. Then extracted data was summarized and reported. The most common application of NFTs in healthcare was found to be in health data management with 46% frequency, followed by supply chain management with 31% frequency. Furthermore, Ethereum is the main blockchain platform that is applied in NFTs in healthcare with 70%.DiscussionThe findings from this review indicate that the NFTs that are currently used in healthcare could transform it. Also, it appears that researchers have not yet investigated the numerous potentials uses of NFTs in the healthcare field, which could be utilized in the future.